Máquina crack - Milonopoulos, Alexis (2014)
Based on a cartographic writing, Crack Machine shows the games of power and the struggling forces within the cracolandia field, pointing out not only the battles, the gears and specific arrangements placed on networks of strategic places, but also dislocations, sinuosity, transversals, tracks, ruts and thresholds that cross the whole cracolandia issue and question our politics. By showing the profusion of useless actions in that area this dissertation treats this matter reaching beyond the discussions about hygienization process and the real estate speculation, pointing out another dimension of the State and the politics and demonstrating a machine that lives off exclusion, speculation, immolation, safety and potentializing more and more lucrative businesses that go from wars against drugs to humanitarianism. In another movement, it exposes the matter of irrecoverable population management, extrapolating the cracolandia space and the discussion about crack cocaine and the control of the undesirable population through technologies that provide administration and risk management. It also shows how these ungovernable populations have been, also with the formation of a new drug market, the main effect of the austerity politics that have taken the globe, questioning our model of society and our political rationality related to the way power has struggled to manage populations since the appearance of the biopower. Taking a step forward from a strictly biopolitical analysis, rewriting the to make die and to let die in the mark of power technologies, pointing out how death became a normal governmental mechanism, inserted in a military-political project of war on drugs and being a privileged strategy that allows the creation of a tension between to make live, to make die and to let die